1998
DOI: 10.1097/00007632-199803010-00001
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Bcl-2 Oncogene Neuronal Expression in the Rat Spinal Cord

Abstract: In vivo Bcl-2 oncogene overexpression was successfully induced in neuronal tissue. After Bcl-2 oncogene expression in the rat spinal cord, the zone of microscopic injury was diminished. Further investigation of the Bcl-2 oncogene for potentially enhancing neuronal survival after spinal cord injury appears indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…This finding is in agreement with previous studies demonstrating that acupuncture could repress apoptosis and promotes functional recovery after SCI [33,35,41]. Motoyama et al confirmed that neurons died in great quantities in Bcl-2-deficient gene mice [16], while more nerve tissues got protection in spinal cords of transferred Bcl-2 gene rats [42]. In contrast, Bax plays a crucial role in promoting cell apoptosis [43] and downregulation of Bax markedly reduces programmed cell death in the Bax knocked-out mice [17,18].…”
Section: The Effects Of Ea On Bax and Bcl-2 Expressionsupporting
confidence: 91%
“…This finding is in agreement with previous studies demonstrating that acupuncture could repress apoptosis and promotes functional recovery after SCI [33,35,41]. Motoyama et al confirmed that neurons died in great quantities in Bcl-2-deficient gene mice [16], while more nerve tissues got protection in spinal cords of transferred Bcl-2 gene rats [42]. In contrast, Bax plays a crucial role in promoting cell apoptosis [43] and downregulation of Bax markedly reduces programmed cell death in the Bax knocked-out mice [17,18].…”
Section: The Effects Of Ea On Bax and Bcl-2 Expressionsupporting
confidence: 91%
“…19,23 One such anti-apoptotic agent, the oncogene Bcl-2, has already been shown to improve histologic survival following an acute experimental spinal cord injury in the rat model. 24 Bcl-2 overexpression was produced invivo following introduction of the Bcl-2 gene via a recombinant adenovirus vector prior to the same experimental spinal cord injury administered in this study. Bcl-2 appears to inhibit apoptotic cell death by regulating an antioxidant pathway that limits free radical generation.…”
Section: Discussionmentioning
confidence: 99%
“…These responses to injury are likely to be mediated and reflected by changes in mRNA concentrations, regardless of whether these changes are due to regulated gene expression or to altered cellular populations. Many investigators have measured the expression of individual genes in injured spinal cords, particularly genes involved with inflammation (1,21,34,42,45,49,52,53), apoptosis (11,33,39,41), excitotoxicity (19,20), and neurotrophin stimulation (21,29,41). None, however, has measured large numbers of genes and their temporal and spatial relationships.…”
mentioning
confidence: 99%